Pengaruh Penerapan Manajemen Mutu Terpadu dan Komitmen Organisasi Terhadap Kinerja Operasional PT. Kereta Commuter Indonesia - Andry Meidianto; Wiwik Rachmarwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
This study was conducted to determine the extent to which the implementation of total quality management and organizational commitment influences on the operational performance of PT. Kereta Commuter Indonesia. The sample used in this study were all technical employees at PT. Kereta Commuter Indonesia. The data analysis techniques used were simple linear regression and multiple regression to measure the simultaneous and partial influence of each independent variable on the dependent variable. The results of the study indicate that both the implementation of total quality management and organizational commitment have a positive and significant influence on operational performance.